Optical-Fiber Power Meter Comparison Between NIST and PTB - Vayshenker, I. (J Res Natl Inst Stand Technol, 2003)
We describe the results of a comparison of reference standards between the National Institute of Standards and Technology (NIST-USA) and Physikalisch-Technische Bundesanstalt (PTB-Germany) at nominal wavelengths of 1300 nm and 1550 nm using an optical-fiber cable. Both laboratories used thermal detectors as reference standards. A novel temperature-controlled, optical-trap detector was used as a transfer standard to compare two reference standards. Measurement results showed differences of less than 1.5 × 10(−3), which is within the combined uncertainty for both laboratories.